Agentes bacterianos causantes de infección de vías urinarias en mujeres que asisten al Hospital Isidro Ayora (Loja) - Celly Campoverde, Tayron Alberto (2018)
Urinary Tract Infection (acronym UTI) is defined as the healthy urinary tract invasion by microorganisms group called uropathogens. They principally affect the female sex, being 14 times more recurrent than in the male case sex. For whole these reasons, the general aim of the present research project was to: To determine the bacterial agents which cause Urinary Tract Infection in women attending the “Isidro Ayora” Hospital (Loja); and as specific objectives: To identify isolated gram-negative bacteria in urine cultures and, to indicate the distribution of agents causing urinary tract infection according to the worker's or user´s age and health service area. The study was being made during the term December 2017- April 2018, and it had had a quantitative approach of a Descriptive, Prospective and Transversal sort. The universe or total consisted of 394 users, and 164 met the inclusion criteria being the sample. Bacterial identification was carried out using the VITEK 2 Compact automated equipment. The principal etiological agents isolated have its place to the group of gram-negative bacilli, which were Escherichia coli (91%), Klebsiella pneumoniae (5%), Proteus mirabilis (3%) and Pseudomona aeruginosa (1%). The most part directly of them affected age groups were adults (50.6%) and elderly adults (26.6%), the areas from which the greatest number of isolation came were the emergency (48.9%) and the external consultation (34.2%). Key words: Urinary tract infection, women, uropathogens, enterobacteria.